2020
DOI: 10.33024/jkm.v6i3.1731
|View full text |Cite
|
Sign up to set email alerts
|

Pemberian Vitamin C Dapat Meningkatkan Kadar Hemoglobin Pada Ibu Hamil Anemia

Abstract: Background: anemia in pregnancy is anemia due to iron deficiency, and is a type of anemia which is relatively easy treatment, even cheap. Efforts to overcome iron nutritional anemia in pregnant women are done through increasing the coverage of iron tablet supplementation, Vitamin C has unstable properties in alkaline solutions, stable in dry conditions and in acidic solutions, and as an iron catalyst so that helps absorption. Preliminary survey conducted by researchers in January 2019 from observations from 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…From the results of the study, it shows that the average Hb level in the group given vitamin C is 12.69 ± 0.89 g/dL, which is significantly higher (p < 0.05) compared to the average hemoglobin (Hb) level in the control group, namely 11.93 ± 1.08 g/dL. This is also consistent with research conducted by Agusmayanti et al (2020), which stated that giving vitamin C can increase Hb levels in pregnant women, so pregnant women were expected to consume vitamin C regularly. However, a cross-sectional study conducted by Habibie et al (2018) stated that there was no relationship between vitamin C intake and hemoglobin (Hb) levels in female adolescents.…”
Section: Vitamin C and Hemoglobin Levels (Hb)supporting
confidence: 89%
“…From the results of the study, it shows that the average Hb level in the group given vitamin C is 12.69 ± 0.89 g/dL, which is significantly higher (p < 0.05) compared to the average hemoglobin (Hb) level in the control group, namely 11.93 ± 1.08 g/dL. This is also consistent with research conducted by Agusmayanti et al (2020), which stated that giving vitamin C can increase Hb levels in pregnant women, so pregnant women were expected to consume vitamin C regularly. However, a cross-sectional study conducted by Habibie et al (2018) stated that there was no relationship between vitamin C intake and hemoglobin (Hb) levels in female adolescents.…”
Section: Vitamin C and Hemoglobin Levels (Hb)supporting
confidence: 89%
“…Hasil penelitian menunjukkan bahwa puasa dapat meningkatkan kekebalan tubuh melalui peningkatan jumlah makrofag, interferon ɤ, penurunan faktor inflamasi maupun peningkatan jumlah bakteri komensalisme di usus. Puasa dapat meningkatkan imunitas terhadap mikroba, walaupun belum ada penelitian tentang dampak puasa pada kekebalan tubuh terhadap virus covid-19 (Agusmayanti et al, 2020). Peningkatan imunitas pada orang yang berpuasa lebih dipicu oleh dipicu oleh status kesehatan umum orang yang berpuasa maupun gaya hidup (Ali M. Farag et al, 2020).…”
Section: Kajian Pustakaunclassified
“…56 Another interventional study found a significant increase of 3.21 g/dL in the hemoglobin level of pregnant women with anemia after being given vitamin C supplementation. 57 In clinical setting, the results of the study can be used as a reference for anemia control programs for pregnant women. Some interventions to reduce the prevalence of low hemoglobin levels in pregnant women need to be started as early as possible, since adolescence period.…”
Section: Original Articlementioning
confidence: 99%